Estudo das microdeformações geradas ao redor de implantes de hexágono externo, sob a aplicação de cargas axiais e não axiais em pilares protéticos retos e angulados - Rodrigues, Vinícius Anéas [UNESP] (2014)
The aim of this in vitro study was to evaluate by strain gauge analysis, the micro-strain distribution around three elements implant supported partial prosthesis with external hexagon implants on axial and non-axial loading and to evaluate possible correlations with gaps found on the metal structures. Two polyurethane blocks were made, received three implants each and divided in two groups: straight and angled 17°. To measure the micro-strain, four strain gauges were bonded on the surface of the blocks tangentially to every implant. Microunit abutments were used for all implants, and the implants with an inclination of 17°, receiving abutment to correct angulations. Plastic copings were adapted to a standard pattern and cast. The metallic structure was screwed onto the abutments using a 10 Ncm torque. A static vertical load was applied 30kgf for 10 seconds with a load application device. The data were analyzed by ANOVA and Tukey's test (p< 0.05%) and related values gaps through the linear Pearson's correlation test. The results showed that the values for different implant inclinations were significant, (p = 0.0022) for axial points and (p = 0.0012) for non-axial points; whereas the point of application of load (p = 0.0001), obtained significant values only for non-axial points, the results showed no correlation between the micro-deformations and gaps. It was concluded that the micro-deformations are higher for the 17° angled implants and to the farthest points of the fastening screw of the structures in non-axial points (3 and 5 mm); there was no correlation found between the gaps and the values of microstrain